2013
DOI: 10.1002/aenm.201300712
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Grain Boundaries in Cu2ZnSnSe4 for Better Cell Performance: A First‐Principle Study

Abstract: Through first‐principle density functional theory (DFT) calculations, the atomic structure and electronic properties of intrinsic and passivated Σ3 (114) grain boundaries (GBs) in Cu2ZnSnSe4 (CZTSe) are studied. Intrinsic GBs in CZTSe create localized deep states within the band gap and thus act as Shockley‐Read‐Hall recombination centers, which are detrimental to cell performance. Defects, such as ZnSn (Zn atoms on Sn sites), Na+i (interstitial Na ions), and OSe (O atoms on Se sites), prefer to segregate into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
118
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(127 citation statements)
references
References 42 publications
5
118
0
2
Order By: Relevance
“…So far, no atomic structure of MAPbI 3 GBs has been reported in experiment. Previous investigation has shown that the electronic structures of GBs in conventional thin-fi lm solar cells [ 44,45 ] such as CdTe, CuInSe 2 , and Cu 2 ZnSnSe 4 are dominated by the anion-anion and/or cation-cation wrong bonds at the GB plane. For MAPbI 3 , we chose Σ3(111) GB and Σ5(310) GB as shown in Figure 2 for study because these two GBs include those wrong bonds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, no atomic structure of MAPbI 3 GBs has been reported in experiment. Previous investigation has shown that the electronic structures of GBs in conventional thin-fi lm solar cells [ 44,45 ] such as CdTe, CuInSe 2 , and Cu 2 ZnSnSe 4 are dominated by the anion-anion and/or cation-cation wrong bonds at the GB plane. For MAPbI 3 , we chose Σ3(111) GB and Σ5(310) GB as shown in Figure 2 for study because these two GBs include those wrong bonds.…”
mentioning
confidence: 99%
“…Both theoretical and experimental observations suggest that Cl is unlikely in the MAPbI 3 bulk. Here, we examined the possibility of Cl at GBs because defect segregation at GBs is the usual phenomenon [ 44,45,[47][48][49] in thin-fi lm solar cells such as CdTe, CuInSe 2 , and Cu 2 ZnSnSe 4 . We found that in Σ5(310) GB, the total energies of Cl I at I-I wrong bond sites are about 0.2 eV lower than that in bulk, as shown in Figure 6 b, indicating that Cl can spontaneously segregate into the GB region.…”
mentioning
confidence: 99%
“…Obviously, the atomic configuration of prototype CSL Σ3 (112) GBs, without carefully accounting for bond rearrangement, is questionable. Similar Σ3 (112) GB models were also used in the study of Σ3 (114) GBs of ternary CuInSe2, 18 Σ3 (114) GBs of quaternary Cu2ZnSnSe4 19 and Σ5 (310) GBs of perovskite CH3NH3PbI3. 20 Therefore, a careful investigation of the possible atomic configurations of Σ3 (114) GBs and their properties is urgently needed and of general importance.…”
Section: Introductionmentioning
confidence: 99%
“…Since current thin-film technologies mostly rely on polycrystalline materials, physical properties of extended defects, especially grain boundaries (GBs) have been investigated to understand their effects on the device efficiency [10][11][12][13][14][15][16]. Other extended defects like stacking faults (SFs) and antisite domain boundaries (ADBs) have been less documented as compared to the GBs, but since SFs in CdTe act as electron barriers and reduce the efficiency [17][18][19][20], SFs in CZTS should be investigated.…”
Section: Introductionmentioning
confidence: 99%